Assessment of the Dentistry undergraduates’ knowledge on tooth avulsion - Evandro Reynard; Felipe Guilherme Jansson; Kauhanna Vianna de Oliveira; Bruno Marques da Silva; Luciana Stadler Demenech; Denise Piotto Leonardi; Flávia Sens Fagundes Tomazinho (Revista Sul-Brasileira de Odontologia, 2016)
Dental trauma affects mainly children, teenagers and young adults and the anterior teeth. In dental avulsion, the teeth are completely displaced out of the socket. This dentoalveolar lesion is that causing the most severe functional, esthetic, and psychologic damage to the patient. Objective: To evaluate the knowledge level of Dentistry undergraduates on tooth avulsion and verify whether the course period would be associated with the knowledge level. Material and methods: A questionnaire adapted from Fujita et al.. [5], was applied, consisting of three parts, Part 1: general demographic data; Part 2: questions about the experience in tooth trauma Part 3: knowledge about tooth avulsion. The questionnaire was applied to 706 Dentistry undergraduates from Positivo University (PR), in June, 2015. The chi-square test was used to identify differences in responses for different variables, with significance level of 5%. Results: Most of the students were at the age range from 16 to 20 years-old (47.1%), were female (74.7%), were not trained on first-aid care in cases of tooth trauma (73.9%), and never faced a case of tooth avulsion (68.8%). The course period was statistically and positively associated with the knowledge on dental avulsion. Conclusion: The evaluated Dentistry undergraduate students knew how to manage cases of tooth avulsion. Statistically significant differences occurred in relation to the course period and the knowledge on tooth avulsion.